PP.14.07: DUAL AT1 RECEPTOR/NEPRILYSIN INHIBITION (ARNI) VS. AT1 RECEPTOR BLOCKADE IN DIABETIC TGR(MREN2)27 RATS. (June 2015) - Roksnoer, L.; Van Veghel, R.; De Vries, R.; Garrelds, I.M.; Bhaggoe, U.M.; Friesema, E.C.H.; Leijten, F.; Hoorn, E.J.; Danser, A.H.J.; Batenburg, W.W.
Abstract : Objective: The recently developed combination of an Angiotensin Receptor blocker (ARB) and a Neprilysin Inhibitor (NEPi) has beneficial effects on clinical progression and mortality of patients with heart failure as compared to enalapril. However, since NEP also degrades endothelin-1 (ET-1), ARNI may cause side effects by increasing the levels of ET-1. Indeed, we recently observed in hypertensive heterozygote TGR(mREN2)27 rats that a low but not a high (0.1 vs. 1.0 mg/kg.day) dose of the NEPi thiorphan reduced blood pressure and cardiac hypertrophy on top of the ARB irbesartan. This was due to the fact that the high dose increased ET-1, upregulated constrictor vascular ET-1 type B receptors and induced an increase in renal sodium–hydrogen exchanger 3 protein abundance. In the present study, we studied the effects of the low thiorphan dose on top of irbesartan in diabetic TGR(mREN2)27 rats. Design and method: Heterozygote TGR(mREN2)27 rats were made diabetic with streptozotocin for 5 or 12 weeks. Rats were treated in the final 3 weeks with vehicle, irbesartan (15 mg/kg.day; IRB) or IRB plus the NEPi thiorphan (0.1 mg/kg.day; ARNI). Haemodynamics were measured by telemetry in the 5 week diabetic animals. In the 12 week diabetic animals vascular reactivity was determined in isolated mesenteric arteries, renal Na+ transporters were analysed by immunoblotting, and plasma and urine were collected for biochemical analysis. Results: Baseline mean arterial blood pressure (MAP) was 156.8 ± 5.4 mmHg. IRB and ARNI lowered MAP identically over the 3-week period, a maximum reduction of ∼50 mmHg being reached around day 7. Heart weight/tibia length ratio was reduced after treatment with ARNI only. Proteinuria and albuminuria were observed from 8 weeks of diabetes onwards and proteinuria was significantly reduced by ARNI treatment only. Urinary volume and plasma and urinary creatinine did not change. No ET-1 rises were observed, vascular reactivity was not influenced, and the pattern of kidney sodium transporters was not affected by ARNI or IRB treatment. Conclusions: ARNI reduces cardiac hypertrophy and proteinuria in diabetic TGR(mREN2)27 rats independently of blood pressure.